The case of the glow-in-the-dark ghost - Preller, James; Smith, Jamie C.; Alley, R. W. (Robert W.) (New York : Scholastic, 2004)
Jigsaw Jones is not afraid of the glowing ghost some students saw in the classroom and he is determined to catch it...even if he has to stay after school to get the job done!
"A Little Apple paperback."
2.0.
006-009.
450
Accelerated Reader AR
Keywords: Ghosts -- Juvenile fiction; Schools -- Juvenile fiction; Mystery fiction